Campur Kode Yang Dilakukan Gibran Pada Talkshow Rosi Episode: Saya Bukan Walikota Karbitan Tapi Bocil Dinasti: Jenis-Jenis Campur Kode, Faktor Penyebab Terjadinya Campur Kode - Maryati. S; Erni, Erni (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Mixing code is the entry of a particular variety of languages into the language being used. In communicating, Gibran often uses more than one language when conveying ideas. The use of a variety of regional languages and foreign languages mixed with the use of Indonesian is an interesting language phenomenon to study. This research was carried out with the aim of explaining the types of fators that cause the emergence of code mixing. The methodology used in this study is content analysis with a qualitative approach. The source of data can be obtained from all the speeches made by Gibran on the Rosi talk show in the implementation of the event. The data collection process in this study involves recording, listening, and recording techniques. Data analysis techniques are focused on the stages of data acquisition (identification) and reduction (reduction) of information contained in the collected data. The results of the analysis of mixed code data carried out by Gibran were found to include: (1) the code mix found is to mix the code inward in the form of using Javanese and mixing the code outward in the form of using English and Arabic; (2) several factors that have an influence on code mixes such as popular terms, prestige, code limitations, and speaking partners.